Temperature dependent EXAFS study on transition metal dichalcogenides MoX2 (X = S, Se, Te). (24th June 2016) - Caramazza, S; Marini, C; Simonelli, L; Dore, P; Postorino, P
Abstract: The local structure of molybdenum dichalcogenide MoX2 (X  =  S, Se, Te) single crystal has been studied by means of multi-edge (Mo, Se, and Te K-edges) extended x-ray absorption fine-structure spectroscopy as function of temperature. The temperature dependences of the interatomic distances Mo–X, Mo–Mo and X–X (X  =  S, Se, and Te) and of the corresponding Debye–Waller factors have been extracted over the 70–500 K temperature range. Exploiting the correlated Einstein model, we found that the Einstein frequencies of Mo–X and X–X bonds obtained by present data are in close agreement with the frequencies of the optical (Raman and infrared) stretching modes for both MoS2 and MoSe2, whereas a significant deviation has been found for MoTe2 . A similar anomaly has been found for the force constants related to the Mo–X bonds in the MoTe2 case. Our findings, accordingly with the results reported in a recent theoretical paper, support the idea that the optical vibrational modes have a dominant role in MoS2 and MoSe2, whereas the effects of acoustic vibrational modes cannot be neglected in the case of MoTe2 .